PREVENTION OF NIPPLE CRACKS OF THE MAMMARY GLAND IN THE EARLY POSTNATAL PERIOD - Marina L. Travina; Alexandr G. Popov; Sergey A. Popov; Elena V. Kulikova (Вопросы современной педиатрии)
Preservation and prolongation of the lactation period is not only a guarantee of the child's full physical and mental development but also one of the most important methods for reducing the risk of developing breast cancer. Problems with the mammary gland nipple in a woman in the early postnatal period lead to a refusal of lactation. We carried out a retrospective analysis (period from 2010 to 2016) of the causes of traumatizing mammary gland nipples in the early postnatal period in 172 women (mean age 29.1 ± 4.3 years). Methods of prevention and treatment of nipple injuries in the early postnatal period have been offered for the lactation period prolongation.